1998
DOI: 10.1111/j.1600-0536.1998.tb05763.x
|View full text |Cite
|
Sign up to set email alerts
|

Contribution to chromium and nickel enrichment during cooking of foods in stainless steel utensils

Abstract: Nickel ingestion can cause exacerbation of dermatitis in patients who are already nickel-sensitive; Chromium (Cr VI) is the 2nd allergen, after nickel. However, stainless steel is widely used in home cookware. In this study, we determined nickel and chromium levels by atomic absorption spectrometry in 11 habitual menus cooked in different grades of stainless steel utensils. We noted a great difference in nickel and chromium intake depending on the menu, and a significant difference between the glass and stainl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 8 publications
(11 reference statements)
2
23
0
Order By: Relevance
“…1,[3][4][5][6][7][8][9][10] For example, Flint and Packirisamy investigated the effects of aging utensils and various foodstuffs on the corrosion behavior of stainless steel, [3][4] whereas Kuligowski and Halperin investigated different types of stainless steels derived from several manufacturers. 5 Kuligowski and Halperin concluded that the amount of nickel released from stainless steel utensils during cooking of highly acidic foods was relatively high.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…1,[3][4][5][6][7][8][9][10] For example, Flint and Packirisamy investigated the effects of aging utensils and various foodstuffs on the corrosion behavior of stainless steel, [3][4] whereas Kuligowski and Halperin investigated different types of stainless steels derived from several manufacturers. 5 Kuligowski and Halperin concluded that the amount of nickel released from stainless steel utensils during cooking of highly acidic foods was relatively high.…”
Section: Introductionmentioning
confidence: 98%
“…The amount of nickel and chromium released were under the tolerable daily intake as recommended by the World Health Organization (i.e., 5 µg Ni/kg body weight). [3][4]6 Several studies have been performed with different outcomes related to CORROSION-JUNE 2001 (1) No systematic studies have been conducted on the effect of plastic deformation on the corrosion properties of stainless steels used for cooking utensils. To develop reference methods and validate test methods, a systematic study dealing with corrosion properties of AISI 304 (1) (UNS S30400) (2) stainless steel as a function of the amount of mechanical deformation was performed.…”
Section: Introductionmentioning
confidence: 98%
“…An increase in chromium concentration of foods was also noted for foods cooked in stainless steel compared to glass saucepans (Accominotti et al 1998). Food chromium concentrations may also decrease with processing such as with milling of grains for flour (Schroeder 1971) In Belgium, human breast milk was found to have a chromium content of 0.18 mg L À1 , thereby providing a daily intake of~0.1 mg.…”
Section: Distribution In Foodsmentioning
confidence: 94%
“…Today, 20% of the female population and 2 to 4% of men are nickel-sensitized. [2] This value was significantly lower in the past. An important responsible factor for this, is the increase of nickel in the diet and its presence in many usual consumer products.…”
Section: Introductionmentioning
confidence: 96%